Resource Allocation of Multi-Satellite Beam Hopping Technology Based on System Capacity Maximization - Qing SHU; Xiaoning ZHANG; Zesong FEI (天地一体化信息网络)
Unlike medium and high earth orbit satellites, LEO satellites have the characteristics of small path loss, low propagation delay and high deployment fl exibility.LEO satellites are widely used in real time services, global internet of things, emergency communication and other fi elds.In order to solved the problems of large diff erences in service demand distribution of terrestrial users and low resource utilization in LEO satellite communication systems, a resource allocation algorithm of LEO multi-satellite beam hopping technology based on convex optimization was proposed, which aimed to maximized the system capacity.For multisatellite beam hopping scenarios in LEO satellite communication system, the beam-hopping technology could fl exibly allocated system resources accorded to user needs.Considered the factor of co-channel interference, the service region division scheme based on load balancing and the inter-satellite resource allocation priority scheme was proposed.In order to improved system capacity and resource utilization, it jointly designed a time and power resource allocation algorithm based on convex optimization.The simulation results showed that the proposed scheme could eff ectively reduced co-channel interference and realized the ondemand allocation of system capacity without causing waste of resources.